Genetic variation in meat production related traits in reindeer (Rangifer t. tarandus) - Muuttoranta, Kirsi; Holand, Øystein; Røed, Knut H.; Tapio, Miika; Nieminen, Mauri; Mäki-Tanila, Asko (Rangifer)
2014